2022
DOI: 10.3390/agriculture12122082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oak Leaf Extract, Biofertilizer, and Soil Containing Oak Leaf Powder on Tomato Growth and Biochemical Characteristics under Water Stress Conditions

Abstract: Drought stress is one of the most significant abiotic stresses on the sustainability of global agriculture. The finding of natural resources is essential for decreasing the need for artificial fertilizers and boosting plant growth and yield under water stress conditions. This study used a factorial experimental design to investigate the effects of oak leaf extract, biofertilizer, and soil containing oak leaf powder on the growth and biochemical parameters of four tomato genotypes under water stress throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Root and shoot dry weight decreased significantly in drought, orange peel and cauliflower wastes could not alleviate the negative effect. The application of oak leaf powder to the tomato in drought conditions affected the root fresh and dry weight positively (Tahir et al, 2022). Application of Bacillus velezensis and orange peel to 20 soybean genotypes significantly increased plant height (14.3%), leaf area (11.4%), total above-ground dry weight (13.2%) and root dry weight (12.5%) (Pacheco da Silva et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Root and shoot dry weight decreased significantly in drought, orange peel and cauliflower wastes could not alleviate the negative effect. The application of oak leaf powder to the tomato in drought conditions affected the root fresh and dry weight positively (Tahir et al, 2022). Application of Bacillus velezensis and orange peel to 20 soybean genotypes significantly increased plant height (14.3%), leaf area (11.4%), total above-ground dry weight (13.2%) and root dry weight (12.5%) (Pacheco da Silva et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The plants were uprooted and rinsed with distilled water, and the lengths of their roots and shoots were measured using a ruler. The fresh weight was determined directly after collection, while the dry weight was measured after achieving a consistent weight after 52 h in a 78 °C oven [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different oak species' leaves have been studied chemically in a number of studies, and the existence of phenolic, flavonoid, and terpenoid compounds has been established. Significant radical scavenging, antimicrobial, and antitopoisomerase abilities were also shown [ [26] , [27] , [28] , [29] , [30] ]. To our knowledge, however, there is no information on the effects of NaOH oak leaf biomass pretreatment on the mechanisms involved in the control of Cd stress.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results, especially those regarding biochemical properties, lipid peroxidation and antioxidant responses, suggested that the amelioration of plant capacity to cope with stress depended on a specific plant-strain interaction. Furthermore, oak leaf extract, biofertilizer, and soil containing oak leaf powder were successfully used to enhance growth and biochemical traits in four tomato genotypes under water stress [12]. The use of oak leaf powder and the extract is particularly interesting since they are low-cost substances, simple to use and represent an environmentally sustainable technique for enhancing tomato resistance to drought.…”
Section: Special Issue Overviewmentioning
confidence: 99%